2003
DOI: 10.1097/00005537-200304000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vocal Fold Scarring in a Canine Model

Abstract: Results indicated that viscoelastic tissue changes may take place before scar maturation in the scarred vocal fold lamina propria and that, although abundant collagen deposition may influence viscoelastic shear tissue properties, disorganization of collagen and elastin fibers, thick bundle collagen formation, or the interplay of several of these factors might also play a contributing role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
208
1
14

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 191 publications
(238 citation statements)
references
References 15 publications
(34 reference statements)
15
208
1
14
Order By: Relevance
“…9 On the other hand, in a chronic scarring model of the vocal fold, the density of HA in the scarred vocal folds seemed to vary among animal studies. In rabbit and canine studies, HA density showed no significant difference in scar compared with normal vocal folds at both two months and six months, 7 whereas HA was found to be significantly reduced in scarred vocal folds with a three-month rat model. 12 These results indicate variations of HA due to species differences and time between insult and evaluation of scar.…”
Section: Human Scarred Vocal Folds 11mentioning
confidence: 81%
“…9 On the other hand, in a chronic scarring model of the vocal fold, the density of HA in the scarred vocal folds seemed to vary among animal studies. In rabbit and canine studies, HA density showed no significant difference in scar compared with normal vocal folds at both two months and six months, 7 whereas HA was found to be significantly reduced in scarred vocal folds with a three-month rat model. 12 These results indicate variations of HA due to species differences and time between insult and evaluation of scar.…”
Section: Human Scarred Vocal Folds 11mentioning
confidence: 81%
“…This period of vocal fold scar maturation was based on data from Rousseau et al, who proposed that it takes 6 months for vocal fold scarring to mature in canine and rat models. 3,4 Six months after the procedure, 0.5 mL of hydrogel solution containing 1 lg of HGF was injected into the scarred vocal folds of four dogs (HGF-treated group) using a transoral intracordal injector, and 0.5 mL of hydrogel solution containing 1 lg of PBS was injected into the scarred vocal folds of the four dogs in the sham group. Because HGF was expected to act on the fibroblast in the lamina propria, hydrogel was carefully injected into the subepithelial layer of the vocal fold.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Rosseau and Thibeault 22,23 studied the scarring process of lamina propria and noticed that pro-collagen was more present in the 2nd month postoperative, with stabilization of levels in the 6th month, the same period in which there were higher density collagen fibers manifested on the surgical wound.…”
Section: Discussionmentioning
confidence: 99%